TEKNOLOGI PENGOLAHAN AIR LIMBAH DENGAN PROSES BIOFILM TERCELUP - Nusa Idaman Said (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
Water pollution in the big cities in Indonesia has shown serious problems. One of the potential sources of water pollution is domestic wastewater that is wastewater from kitchens, laundry, bathing and toilets. These problems have become more serious since the spreads of sewerage systems are still low, so that domestic, institutional and commercial wastewater cause severe water pollution in many rivers or water body. This paper describes alternative technology for treatment of wastewater or organic wastewater using submerged biofilter. Using anaerobic and aerobic submerged biofilter within total one day residence time can decrease BOD, COD and Suspended Solids (SS) concentration more than 90 %.